Performance of reduced graphene oxide/iron(III) oxide/silica dioxide (rGO/Fe3O4/SiO2) as a potential oxygen reduction electrocatalyst in fuel cell - Farhanini Yusoff; Karthi Suresh (Penerbit Universiti Kebangsaan Malaysia, 2021)
Synthesis of the nanocomposite comprises reduced graphene oxide, iron (III) oxide and silica dioxide nanocomposites which were denoted as rGO/Fe3O4/SiO2. The acquired nanocomposite was determined to be a substitute for platinum electrode in oxygen reduction reaction (ORR) to catalyze reaction, as usage of platinum causes disadvantages in production. The nanocomposite was analyzed physically and electrochemically to ensure the quality of the synthesized compound. Fourier transform-infrared spectroscopy (FTIR) shows the presences of functional groups such as O-H hydroxyl group, C=C, C=O and existence of silica peak in the spectra of rGO/Fe3O4/SiO2, where the data is also supported by SEM-EDS. Raman Spectrophotometer shows the structural change of three different graphene related materials as modification took place and X-Ray Diffraction (XRD) analysis confirms the reduction of GO into rGO, where the crystalline structure decreased significantly approximately about 10 nm. This data supported with Brunauer-Emmett-Teller (BET) analysis through surface area examination. The compound of rGO/Fe3O4/SiO2 was drop-casted onto glassy carbon electrode (GCE) for modification into rGO/Fe3O4/SiO2/GCE to carry out electrochemical analysis where Cyclic Voltammetry (CV) shows current response by modified electrode is greater than bare GCE while Electron Impedance Spectroscopy (EIS) of same modified electrode affirms the sample underwent reversible process with stable and rapid electron transfers with minimal resistance charge transfer (RCT). The study of ORR was carried out and observed a good electrochemical response of the nanocomposite when purged with oxygen gas.